IPSS-independent prognostic value of plasma CXCL10, IL-7 and IL-6 levels in myelodysplastic syndromes - Pardanani, A (Nature Publishing Group, 2012)
Recent studies suggest a powerful prognostic value for plasma cytokine levels in primary myelofibrosis (interleukin (IL)-2R, IL-8, IL-12, IL-15 and C–X–C motif chemokine 10 (CXCL10)) and large-cell lymphoma (IL-2R, IL-8, IL-10, IL-12, CXCL9 and CXCL10). To examine the possibility of a similar phenomenon in myelodysplastic syndromes (MDS), we used multiplex enzyme-linked immunosorbent assay to measure 30 plasma cytokines in 78 patients with primary MDS. Compared with normal controls (n=35), the levels of 19 cytokines were significantly altered. Multivariable analysis identified increased levels of CXCL10 (P<0.01), IL-7 (P=0.02) and IL-6 (P=0.07) as predictors of shortened survival; the survival association remained significant when the Cox model was adjusted for the International Prognostic Scoring System, age, transfusion-need or thrombocytopenia. MDS patients with normal plasma levels of CXCL10, IL-7 and IL-6 lived significantly longer (median survival 76 months) than those with elevated levels of at least one of the three cytokines (median survival 25 months) (P<0.01). Increased levels of IL-6 were associated with inferior leukemia-free survival, independent of other prognostic factors (P=0.01). Comparison of plasma cytokines between MDS (n=78) and primary myelofibrosis (n=127) revealed a significantly different pattern of abnormalities. These observations reinforce the concept of distinct and prognostically relevant plasma cytokine signatures in hematological malignancies.